Properties and structure of polypropylene/ Polyethylene-octene elastomer/nano CaCO 3 composites - H., Hanim; Fuad, M. Y. A.; R., Zarina; Ishak, Z. A. M.; Hassan, Azman (SAGE Publications, 2008)
Polypropylene (PP)-based nanocomposites were developed by the incorporation of a novel nano-sized precipitated calcium carbonate (NPCC) nanoparticles and polyethylene-octene elastomer (POE). The NPCC filler loading selected were 10 and 15wt.% while the POE contents were varied between 0 and 30wt.%. A slight decrease in the tensile strength of the PP nanocomposites was observed with increasing NPCC content. Results of impact strength indicated that the NPCC filler imparted some toughening effects on the PP and PP/POE blends. Maximum impact strength enhancement was achieved for the PP when blended with 30wt.% POE and filled with 15wt.% NPCC. However, the essential property balance between toughness and stiffness was still lacking in the nanocomposites developed. Differential Scanning Calorimeter results showed that NPCC acted as a nucleating agent for PP, increasing the crystallization temperature of PP by approximately 9Â°C.